Chapter Tensioni tra tecniche e valori nella disciplina delle tutele sociali dei lavoratori flessibili - D'ONGHIA, MADIA (Studi e saggi, 2022)
The essay deals with the social protections of atypical workers that represent an extraordinary proof of the link between values and regulatory techniques. The author points out that current legislation does not always provide adequate forms of social protection for atypical workers. For this reason, often, more effective protections have been recognized in the jurisprudential. Three examples are analyzed: 1) the extension of the principle referred to in art. 2116 of the Italian Civil Code, as well as subordination; 2) the method of calculating the contributory seniority in the vertical part-time for retirement purposes; 3) the right to family allowances for permanent temporary workers. The author provides several points of reflection on the close intertwining of flexibility and social protections and on the need to move the plane of reasoning beyond the contract; it links rights and protections directly to the person entering the labour market and releases them from the status of worker.